In the confusion of time. Representation of Spaniard immigrant in the novel Exilio, of Sara García Iglesias(1957) (2009)
The subjective reconfiguration that suffered Latin America in the decade of the fifties – as consequence of the revenue of the woman to the field of cultural production and the arrival of great European migratory masses – needed a discursive response on t